PERCEPTION LEVEL OF SCAVENGERS ON THE USE OF SUNSCREEN AND PREVENTION OF SKIN CANCER IN OSASCO, SP, 2007-2008 (Fiep Bulletin - online, 2011)
Skin cancer is a neoplasm that, despite being the most common in Brazil, when detected early, has a large percentage of healing. This study was conducted in Osasco, and the aim is to evaluate the level of scavenger's knowledge on the occurrence of skin cancer and the use of sunscreen, as well as know the level of orientation they receive from the company related to skin cancer. For the study, counted on a convenience sample of twenty-nine scavengers (n=29) that, after being informed of the objectives and importance of this research, gave their consent by filling the Free and Clear Consent Statement, based on Nº 196/96 National Health Council Resolution and a questionnaire that aimed to assess perception level of research people with the occurrence of skin cancer and sunscreen use. It was observed that 55% of respondents were male; 52% were mulattoes / black; 55% had some knowledge about skin cancer; 59% report making use of sunscreen, because the company develops a program to promote health; 82% use other forms of protection, addition to sunscreen (cap / hat).